Maternal Mortality in Basra City from 2014 to 2018 - Mohammed, Halah Muzahem; Shiaa, Nadeem Raheem; Hussein, Riyadh Abdul-Ameer (Scientific Journal of Medical Research, 2020)
Background: Worldwide maternal mortality still high, especially in developing countries. The maternal mortality act as an indicator of the quality of maternity care in society, the health status of women, and above all the development of a nation. Objectives: The aims of this study were to estimate maternal mortality ratio in Basra from 2014-2018, define the main causes of maternal deaths; describe sociodemographic factors of dead mothers, features related to pregnancy and death. Methods: A descriptive, retrospective registries based study Data were collected from the vital registration of Basra governorate and hospitals’ medical records through a structured questionnaire applied by the researcher. Results: During the five years period included in the study (2014-2018) there were 206 cases of maternal deaths. Obstetrical haemorrhage was the top cause of maternal death 31.6% followed by pulmonary embolism 10.2%. Conclusion: Maternal mortality in Basra still unacceptably high. Obstetric haemorrhage is still the main cause of maternal deaths in Basra.